2009
DOI: 10.1096/fasebj.23.1_supplement.565.4
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic study of the absorption and metabolism of Montmorency tart cherry anthocyanins in human subjects

Abstract: Anthocyanins found in tart cherries have been shown to function as antioxidants and anti‐inflammatory agents. The in vivo bioavailability of anthocyanins from the ingestion of whole fruits or vegetables and their potential biologic effects have not been well characterized.This study was designed to investigate the pharmacokinetics of anthocyanins in healthy human subjects following the ingestion of a measured dose of tart cherries. We quantified five major anthocyanin compounds in Montmorency cherries as cyani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…As such, although the amount of consumed supplement was monitored, the bioavailability of anthocyanins from the ingestion of tart cherries was unknown. Uhley et al [63] have shown that anthocyanin metabolites can be identified in human blood and urine using liquid chromatography-mass spectrometry analyses. Therefore, future trials investigating the effects of tart cherry supplementation should seek to examine the extent of anthocyanin absorption.…”
Section: Discussionmentioning
confidence: 99%
“…As such, although the amount of consumed supplement was monitored, the bioavailability of anthocyanins from the ingestion of tart cherries was unknown. Uhley et al [63] have shown that anthocyanin metabolites can be identified in human blood and urine using liquid chromatography-mass spectrometry analyses. Therefore, future trials investigating the effects of tart cherry supplementation should seek to examine the extent of anthocyanin absorption.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that cyanidin-3-glycosides are metabolized as glucuronidated and methylated versions of the parent compounds, which affect absorption and molecule redox (50). On the other hand, Uhley and co-workers (51) showed that the consumption of whole fruit tart cherries by healthy humans resulted in the appearance of two unmodified anthocyanins in plasma: cyanidin-3-glucosylrutinoside and cyanidin-3-rutinoside. In another study, researchers suggested that 3-O-β-rutinosyl anthocyanins, including C3R, were directly absorbed and distributed to the blood (52).…”
Section: Discussionmentioning
confidence: 99%